Clinical Utility of a Structured Program to Reduce the Risk of Health-Related Quality of Life Impairment after Discharge from Intensive Care Unit: A Real-World Experience. (8th May 2018) - Venni, Angelica; Ioia, Francesca; Laviola, Silvia; Frigieri, Francesca; Pieri, Alessandra; Marilli, Simona; Balzi, Daniela; Ballo, Piercarlo; Gori, Stefano; Guarducci, Diletta
Abstract : Background . Postdischarge deterioration in health-related quality of life (HRQoL) is a major clinical issue for patients after an intensive care unit (ICU) hospitalization. A significant proportion of these patients is known to develop a progressive worsening of mental and physical performance—the so-called post-intensive care syndrome (PICS). Aim . We aimed at exploring the effects of a structured program for the management of ICU patients, aimed at improving postdischarge HRQoL and reducing the risk of PICS. Methods . A total of 159 patients hospitalized in our ICU with a length of stay >72 hours were enrolled in an institutional management protocol including specific recommendations: adequate sedation and analgesia protocols, to ensure a valid delirium prevention strategy, and to provide a planned midterm after discharge. The main endpoint was the occurrence of PICS at the 6-month follow-up visitation, defined as an abnormal physical or mental score in the SF-12 questionnaire in the presence of clinical evidence of new or worsening impairment in physical, cognitive, or mental health status. An additional questionnaire was administered, to assess the effects of ICU-related memories. Results . Most patients positively rated their health at the 6-month follow-up and had no significant impairment in physical or mental health status. The mean normalized values of the physical and mental component of the SF-12 score were 46 ± 11 and 48 ± 14, suggesting a normal physical and mental health status in most patients. Twenty-nine patients (18.2%) showed evidence of PICS. Similar good results were found by the questionnaire of memories. In multivariable analysis, no variable was found to predict the risk of PICS in our population. Conclusion . In this real-world analysis that lacks a control group, patients who used a program aimed at minimizing the risk of HRQoL deterioration and PICS reported a good perception of their state of health with a relatively low prevalence of PICS.